2001
DOI: 10.1002/dmrr.182
|View full text |Cite
|
Sign up to set email alerts
|

Thymic expression of insulin-related genes in an animal model of autoimmune type 1 diabetes

Abstract: Background Insulin and multiple other autoantigens have been implicated in the pathogenesis of autoimmune type 1 diabetes, but the origin of immunological self-reactivity specifically oriented against insulin-secreting islet b-cells remains obscure. The primary objective of the present study was to investigate the hypothesis that a defect in thymic central T-cell selftolerance of the insulin hormone family could contribute to the pathophysiology of type 1 diabetes. This hypothesis was investigated in a classic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…Transplantation of the thymus and thymic epithelium from the NOD mouse (an animal model of type 1 diabetes) was shown to induce insulitis in recipient athymic ÔnudeÕ mice (47,48). A defect of Igf2 transcription was also demonstrated in the thymus of more than 80% of diabetesprone BB rats (another animal model of type 1 diabetes), in close accordance with the incidence (86%) of autoimmune diabetes in this rat strain (49). The influence of VNTR on IGF2 expression has been analysed in leucocytes, and no difference in IGF2 mRNA levels was observed between protective class III and susceptible class I VNTR alleles (50).…”
Section: Implications For Pathogenesis Of Type 1 Diabetessupporting
confidence: 62%
“…Transplantation of the thymus and thymic epithelium from the NOD mouse (an animal model of type 1 diabetes) was shown to induce insulitis in recipient athymic ÔnudeÕ mice (47,48). A defect of Igf2 transcription was also demonstrated in the thymus of more than 80% of diabetesprone BB rats (another animal model of type 1 diabetes), in close accordance with the incidence (86%) of autoimmune diabetes in this rat strain (49). The influence of VNTR on IGF2 expression has been analysed in leucocytes, and no difference in IGF2 mRNA levels was observed between protective class III and susceptible class I VNTR alleles (50).…”
Section: Implications For Pathogenesis Of Type 1 Diabetessupporting
confidence: 62%
“…Igf2 transcripts were also present in the thymus from all BBDR rats, but were not detected in the thymus from more than 80% of BBDP rats, in close concordance with the incidence (86%) of autoimmune diabetes in those rats. This defect in Igf2 transcription in BBDP thymus could also explain both their lymphopenia (including CD8+ T cells and RT6+ Treg) and the absence of central self-tolerance to insulin-secreting islet β cells [41, 42]. As already mentioned, we have shown that susceptibility to autoimmune diabetes is correlated with the level of Ins2 transcription in the mouse thymus [6].…”
Section: The Central Role Of a Thymus Dysfunction In T1d Pathogenementioning
confidence: 78%
“…Ins and Igf1 transcripts were detected in all BBDP and BBDR thymi whereas Igf2 transcripts were also detected in all BBDR thymi but in only in 4 of 15 BBDP thymi. Such a defect of Igf2 transcription in BBDP thymus could contribute both to their lymphopenia (including CD8+ T and RT6+ Treg cells) and to the absence of central tolerance to islet β cells (Kecha-Kamoun et al, 2001). In humans, INS transcripts are measured at a lower level in the thymus from fetuses with short class I variable number of tandem repeat (VNTR) alleles, the second genetic trait ( IDDM2 ) of T1D susceptibility (Pugliese et al, 1997; Vafiadis et al, 1997).…”
Section: A Defect Of Central Self-tolerance As the Primary Event Drivmentioning
confidence: 99%
“…In this context, infusion of a strongly active insulin mimetope was recently shown to convert naïve T cells into Foxp3+ Treg cells in vivo and to prevent autoimmune diabetes in NOD mice (Daniel et al, 2011). We proposed that IGF-2 could be a safer and more valuable basis for developing a specific “negative/tolerogenic self-vaccination,” on the basis that Igf2 transcription is defective in the thymus of BBDP rats (Kecha-Kamoun et al, 2001) and that IGF-2 mediates significant cross-tolerance to insulin (Hansenne et al, 2006). The concept of negative self-vaccination implies both the competition between IGF-2 and insulin-derived epitopes for presentation by DQ2 and DQ8 alleles, as well as a tolerogenic response—including recruitment of Treg cells–induced by MHC-presentation of IGF-2 self-peptides (Geenen et al, 2004, 2010).…”
Section: The Concept Of “Negative/tolerogenic Self-vaccination”mentioning
confidence: 99%